Penggunaan Gimkit Pada Pembelajaran IPA SMP Terhadap Motivasi Belajar Peserta didik - Nur Hikmah; Yudha Irhasyuarna; Ellyna Hafizah (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2026)
This study aims to find out whether there are differences in the level of learning motivation between students who use Gimkit interactive media and students who do not use Gimkit on the human circulatory system material. A quasi-experimental design method was used with two classes, each consisting of 26 students. Motivation questionnaires, observation sheets, and learning outcome tests were the data collection techniques in this study. Data analysis was carried out through processing motivation scores and learning outcomes, accompanied by statistical tests used to see significant differences between the two classes. The results showed that learning motivation increased in the experimental class from 69% to 85% (high category), while in the control class it only increased from 64% to 69% (low category). There was a significant difference between the two groups, because the sig. score value (2-tailed) was 0.00 < 0.05 from the Independent sample test. Observation data and learning outcomes also supported this finding. It was concluded that high learning motivation during learning was the cause of increased student learning outcomes.